A comparative study of monoaxial and coaxial PCL/gelatin/Poloxamer 188 scaffolds for bone tissue engineering. Issue 6 (12th April 2020) - Alissa Alam, Hani; Dalgic, Ali Deniz; Tezcaner, Aysen; Ozen, Can; Keskin, Dilek
Abstract: Structure of fibrous scaffolds varies depending on the electrospinning method and parameters which will define cell fate. In this study, monoaxial and coaxial electrospun PCL/gelatin/P-188 scaffolds were characterized in terms of morphology, chemistry, mechanical property, water retention, weight loss, porosity and release properties. Coaxial fibers supported duel release of model hydrophilic protein (Beta-lactoglobulin) and hydrophobic agent vitamin K2. Novel PCL/P-188(Shell):Gelatin/P-188(Core) coaxial scaffold had superior stability, average weight loss, no swelling behavior, controlled release of Beta-lactoglobulin and vitamin K2, enhanced Saos-2 cell viability and ALP activity and could be a good candidate as a bone tissue scaffold. Graphical Abstract: